Large-scale lipidomics identifies associations between plasma sphingolipids and T2DM incidence - Wee Siong Chew; Federico Torta; Shanshan Ji; Hyungwon Choi; Husna Begum; Xueling Sim; Chin Meng Khoo; Eric Yin Hao Khoo; Wei-Yi Ong; Rob M. Van Dam; Markus R. Wenk; E. Shyong Tai; et al. (JCI Insight, 2019)
BACKGROUND Sphingolipids (SPs) are ubiquitous, structurally diverse molecules that include ceramides, sphingomyelins (SMs), and sphingosines. They are involved in various pathologies, including obesity and type 2 diabetes mellitus (T2DM). Therefore, it is likely that perturbations in plasma concentrations of SPs are associated with disease. Identifying these associations may reveal useful biomarkers or provide insight into disease processes.METHODS We performed a lipidomics evaluation of molecularly distinct SPs in the plasma of 2302 ethnically Chinese Singaporeans using electrospray ionization mass spectrometry coupled with liquid chromatography. SP profiles were compared to clinical and biochemical characteristics, and subjects were evaluated with follow-up visits for 11 years.RESULTS We found that ceramides correlated positively but hexosylceramides correlated negatively with BMI and homeostatic model assessment of insulin resistance (HOMA-IR). Furthermore, SPs with a d16:1 sphingoid backbone correlated more positively with BMI and HOMA-IR, while d18:2 SPs correlated less positively, relative to canonical d18:1 SPs. We also found that higher concentrations of 2 distinct SMs were associated with a higher risk of T2DM (HR 1.45 with 95% CI 1.18–1.78 for SM d16:1/18:0 and HR 1.40 with 95% CI 1.17–1.68 for SM d18:1/18:0).CONCLUSIONS We identified significant associations between SPs and obesity/T2DM characteristics, specifically, those of hexosylceramides, d16:1 SPs, and d18:2 SPs. This suggests that the balance of SP metabolism, rather than ceramide accumulation, is associated with the pathology of obesity. We further identified 2 specific SPs that may represent prognostic biomarkers for T2DM.FUNDING National University Health System (NUHSRO/2014/085/AF-Partner/01) and the National Research Foundation Investigatorship grant (NRF-NRFI2015-05).